Critical Review Faktor Pendorong, Penghambat dan Regulasi Implementasi Green Campus Pada Perguruan Tinggi di Indonesia - Kurniawati, Tri; Khaidir, Afriva (Jurnal Ecogen, 2025)
This study aims to explore the driving, inhibiting and regulatory factors regarding green campuse implementation at universities in Indonesia. This study used a systematic literature review with PRISMA and VosViewer.  The results of this study show that there are various driving and inhibiting factors that influence the success of the green campus program in higher education institutions in Indonesia. The main driving factors include the existence of supportive regulations as well as the commitment from management and the academic community to implement environmentally friendly practices. Initiatives such as campaigns to reduce plastic use, recycling programs, and restrictions on the use of motor vehicles also contribute positively to achieving the goals of a green campus. However, challenges such as a lack of supportive leadership, resistance to change, and insufficient knowledge and understanding of sustainability pose significant obstacles. Therefore, to achieve effective implementation of the green campus, collaborative efforts from all parties are needed, including strengthening regulations, raising awareness, and better management support.